A „cudar porkoláb”: Az irodalom „mellékállásainak” kritikai következményei a 20. század elején - Rákai, Orsolya (Studia Litteraria, 2021)
By the end of the 19th century, the writer’s former ‘normal career’, i.e. the wealth provided by social status, which helped to create the freedom and leisure time necessary for writing, had been transformed. However, the perception of the jobs that replaced it was not uniform in the authors’ descriptions. Through the examples of three early 20th century authors, Margit Kaffka, Mihály Babits and Zsigmond Móricz, I seek to answer the question of how the desire to preserve the elite position of literature influenced the notions of work, ‘productivity’ and pro+t in the perception of the value of a writer’s career.